2015
DOI: 10.1039/c5py00990a
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy-telechelic poly(ethylene-co-isobutylene) as a soft segment for thermoplastic polyurethanes

Abstract: Facile preparation of linear amorphous hydroxy-telechelic poly-(ethylene-co-isobutylene) (PEIB) was enabled by ROMP of a new monomer, (Z)-5,5-dimethylcyclooct-1-ene (Me 2 COE). Control of the equivalent isobutylene content and the resulting thermal properties was accomplished via copolymerization with COE. The applicability as a prepolymer was demonstrated by the synthesis of a tough, elastic and free-standing polyurethane film. cyclooctadiene (1,5-COD), as shown in Scheme 1. tert-Butyl Scheme 1 Synthesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 27 publications
1
42
0
1
Order By: Relevance
“…13,16 Synthesis of Methyl (Z)-Cyclooct-4-ene-1-Carboxylate (MEC) This known compound was prepared via a slightly different procedure from Wagener and coworkers and the spectral ARTICLE data were in accordance with literature data. 13 In a 1-L high pressure reactor (Series 4520 Bench Top Reactors, 1L, Parr Instrument Company), palladium (II) chloride (2.9 g, 16.3 mmol), triphenylphosphine (17 g, 64.8 mmol), anhydrous methanol (42 mL, 1038 mmol), 1,5-cyclooctadiene (COD, 200 mL, 1630 mmol) and toluene (100 mL) were placed.…”
Section: Synthesis Of the Monomers Bec And Mmecmentioning
confidence: 99%
See 2 more Smart Citations
“…13,16 Synthesis of Methyl (Z)-Cyclooct-4-ene-1-Carboxylate (MEC) This known compound was prepared via a slightly different procedure from Wagener and coworkers and the spectral ARTICLE data were in accordance with literature data. 13 In a 1-L high pressure reactor (Series 4520 Bench Top Reactors, 1L, Parr Instrument Company), palladium (II) chloride (2.9 g, 16.3 mmol), triphenylphosphine (17 g, 64.8 mmol), anhydrous methanol (42 mL, 1038 mmol), 1,5-cyclooctadiene (COD, 200 mL, 1630 mmol) and toluene (100 mL) were placed.…”
Section: Synthesis Of the Monomers Bec And Mmecmentioning
confidence: 99%
“…2,16 A solution of methyl (Z)-cyclooct-4-ene-1-carboxylate (30.0 g, 178 mmol) in 150 mL dry tetrahydrofuran was slowly added to a lithium diisopropylamide solution (LDA, 2 M in THF/heptane/ethylbenzene, 135 mL, 270 mmoles) over 30 min with a syringe at 278 8C. The reaction was stirred at 278 8C for 15 min and then slowly warmed up to 0 8C over 30 min by removing the acetone-dry ice bath.…”
Section: Synthesis Of Methyl (Z)-1-methylcyclooct-4-ene-1-carboxylatementioning
confidence: 99%
See 1 more Smart Citation
“…However, they still undergo hydrolytic degradation . Polyolefin‐based polyols are another important kind of hydrophobic polyols, such as hydroxyl‐telechelic polyisobutylene (PIB), hydroxyl‐telechelic poly(ethylene‐ co ‐isobutylene), and hydroxyl‐terminated polybutadiene (HTPB) . It was reported that PIB‐based PU with 75% PIB soft segment exhibited lower water absorption (tertiary carbon with two methyl offering high barrier) and far superior hydrolytic stability than that of the commercially available PDMS‐based PU (Elast‐Eon E2A) .…”
Section: Introductionmentioning
confidence: 99%
“…The saturated hydrocarbon backbone is responsible for many advantageous properties of PIB, but it also limits the ability to modify and tune the properties of the polymer. Thus, many applications of PIB have involved the introduction of chemical functionalities to the PIB backbone or termini, or the incorporation of PIB into block copolymers . For example, IB can be copolymerized with small amounts (i.e.…”
Section: Introductionmentioning
confidence: 99%